Walter Hopps's Los Angeles pastoral - Bradnock, Lucy E. (College Art Association, 2012)
An intriguing tale crops up in oral history interviews conducted with Los Angeles artists and curators of the 1950s. Recounted by the curator Walter Hopps, the artist Craig Kauffman, and the gallerist Jim Newman, it concerns a Midwestern farmer, who, in the early hours of a morning in the early 1950s, stepped in front of a truck on a quiet rural road and was killed. Hopps locates the incident in Nebraska in 1952, Kauffman in Ohio in 1954, and Newman in Indiana in 1953.